Development of a prognostic prediction model incorporating KDM1B for esophageal squamous cell carcinoma: an integrated transcriptomic and functional analysis - Sun, Zhiwei; Yang, Ying; Yu, Jing; Shi, Youwu; Sun, Jing; Du, Feng; Xiao, Yanjie; Gao, Songlin; Zhang, Xiaodong; Jia, Jun (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: KDM1B, a flavin-dependent histone demethylase, is an epigenetic regulator implicated in tumorigenesis; however, its role in esophageal squamous cell carcinoma (ESCC) remains unclear. We aimed to explore the biological role of KDM1B in ESCC and, on this basis, to develop a prognostic prediction model incorporating KDM1B.Methods: Public transcriptomic and clinical data from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO; GSE26886 and GSE161533) were analyzed to assess KDM1B expression, prognostic relevance, pathway enrichment, and immune infiltration in ESCC. KDM1B genomic alterations were further examined in 52 ESCC specimens from our center. Functional assays were performed in ESCC cell lines to evaluate the effects of KDM1B on proliferation, migration, and apoptosis. Overall survival (OS) was the primary prognostic outcome. Univariable and multivariable Cox regression analyses were performed to construct a prognostic prediction model for estimating 1-, 3-, and 5-year OS.Results: KDM1B was significantly upregulated in ESCC compared with normal esophageal epithelium and was associated with a higher response rate to systemic therapy. In our cohort, intronic variants and copy-number alterations of KDM1B were detected in a subset of tumors. Functional enrichment analyses suggested that KDM1B may be involved in cell-cycle regulation and apoptosis, and its expression was associated with immune infiltration. Survival analyses showed that elevated KDM1B expression was associated with longer OS. A prognostic prediction model incorporating KDM1B expression, pathologic node stage (N stage), pathologic metastasis stage (M stage), overall pathologic stage, gender, and histologic grade was developed to estimate 1-, 3-, and 5-year OS in patients with ESCC. In vitro experiments showed that KDM1B promoted ESCC cell proliferation and migration while inhibiting apoptosis, suggesting a context-dependent role in ESCC biology, potentially influenced by treatment and the immune microenvironment.Conclusions: KDM1B is upregulated in ESCC and may influence tumor behavior through regulation of the cell cycle, apoptosis, and the tumor immune microenvironment. KDM1B was also incorporated into a prognostic prediction model for OS estimation in ESCC, supporting its potential value in prognostic stratification.